READINESS FOR INNOVATIVE ACTIVITIES AS AN IMPORTANT PROFESSIONAL QUALITY OF THE FUTURE MUSIC TEACHER - Леонова, О.М.; Черкасова, С.О. (Modern engineering and innovative technologies, 2023)
The article describes the problems of implementing innovative technologies in the training of a future music teacher. The principles of innovative activity of the future music teacher are considered. Indicators of students' readiness for innovative activi